ANALISIS FAKTOR PENYEBAB RENDAHNYA MINAT SISWA DALAM MATA PELAJARAN PPKN DI MA AT-THOYYIBIYAH - Faweid Faweid; Dian Eka Indriani (Jurnal Manajemen Pendidikan, 2026)
Low interest in learning Civic Education (PPKn) has become one of the challenges that may hinder the achievement of citizenship education objectives and the development of students' character. This study aims to analyze the factors contributing to students' low interest in Civic Education at MA At-Thoyyibiyah. The research employed a descriptive qualitative approach involving the principal, Civic Education teacher, and students as research informants. Data were collected through observation, in-depth interviews, and documentation, and subsequently analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that students' low learning interest was influenced by both internal and external factors. Internal factors included low learning motivation, inadequate learning readiness, and students' attitudes and perceptions that Civic Education is predominantly theoretical and memorization-oriented. External factors consisted of the teacher's role, teaching methods, and the school environment. The study found that low learning motivation was the most dominant internal factor, while less varied teaching methods were the most influential external factor affecting students' learning interest. The novelty of this study lies in the identification of dominant factors causing low interest in Civic Education through the simultaneous perspectives of the principal, teacher, and students, thereby providing a more comprehensive understanding of learning interest issues within the secondary education context. The findings are expected to serve as a basis for developing more innovative and participatory learning strategies to enhance students' interest in Civic Education.